1984
DOI: 10.1111/j.1471-4159.1984.tb12843.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Calcium Accumulation and Cation Shifts in Rat Brain by Kainate

Abstract: Following local application of kainic acid, changes in the contents of Na+, K+, Ca2+, and Mg2+ of the striatum, cerebellum, and hippocampus of the rat were observed at various times after surgery. Within 1 h the levels of K+ decreased 20% whereas the levels of Na+ and Ca2+ increased at least 50% and 20%, respectively. These changes persisted for more than 8 weeks. Ca2+ levels rose further, to more than 10-fold during 8 weeks. The Mg2+ levels were slightly and only transiently decreased. Unilateral injections o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…The analyses by X-ray and electron microscopy have shown that Alizarine Red-stained precipitates are largely composed of calcium and phosphate in the form of hydroxyapatite (Herrmann et al, 1998;Mahy et al, 1995Mahy et al, , 1999; small (around 2 µm mean diameter) and medium (around 4 µm mean diameter) sized deposits can be observed intracellularly whereas the larger ones (around 21 µm diameter), that have psammon body-like appearance, are extracellular (Mahy et al, , 1999. This calcium deposition has been reported to be an excitotoxin-and area-selective mechanism with a progressive character: the deposits growing in size and number at long term after excitotoxin injection (Herrmann et al, 1998;Korf and Postema, 1984;Mahy et al, 1995;Nitsch and Schaefer, 1990;Saura et al, 1995). Regional differences in the formation of calcium deposits have been related to local differences in glial compensatory mechanisms or to differences in calcium buffering and storage; for instance development of calcium concretions has been associated with predominant microglial reaction and lack of such deposits with astrogliosis and tissue atrophy (Saura et al, 1995).…”
Section: Discussionmentioning
confidence: 93%
“…The analyses by X-ray and electron microscopy have shown that Alizarine Red-stained precipitates are largely composed of calcium and phosphate in the form of hydroxyapatite (Herrmann et al, 1998;Mahy et al, 1995Mahy et al, , 1999; small (around 2 µm mean diameter) and medium (around 4 µm mean diameter) sized deposits can be observed intracellularly whereas the larger ones (around 21 µm diameter), that have psammon body-like appearance, are extracellular (Mahy et al, , 1999. This calcium deposition has been reported to be an excitotoxin-and area-selective mechanism with a progressive character: the deposits growing in size and number at long term after excitotoxin injection (Herrmann et al, 1998;Korf and Postema, 1984;Mahy et al, 1995;Nitsch and Schaefer, 1990;Saura et al, 1995). Regional differences in the formation of calcium deposits have been related to local differences in glial compensatory mechanisms or to differences in calcium buffering and storage; for instance development of calcium concretions has been associated with predominant microglial reaction and lack of such deposits with astrogliosis and tissue atrophy (Saura et al, 1995).…”
Section: Discussionmentioning
confidence: 93%
“…Whether calcium influx is a direct cause of, or a secondary result of cell death in the nervous system remains a matter of controversy [7][8][9]. Nonetheless, there is good evidence that the calcium influx following repetitive hippocampal stimulation by chemical or electrical means, is the event that leads to regional necrosis [10,11]. In cerebellar slices, the neurotoxicity of excitatory amino acid agonists can be dependent on calcium concentration [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, calcium influx may accompany toxic effects in nerve cells without necessarily being the cause of cell death. Thus, the accumulation of insoluble calcium deposits is associated with many types of neurological damage including seizures (23), spinal cord injury (5), uremia (2), aluminum encephalopathy (20), lead poisoning (53), and kainic acid treatment (33). In any event, [Ca 2 +]; can often serve as an effective indicator of imminent cell death (15).…”
Section: Elevationmentioning
confidence: 99%